VARIASI PH PADA MEDIA TUMBUH DAN SUHU FERMENTASI DALAM MEMPRODUKSI ETANOL OLEH ISOLAT BU3.111E1 - Malau, Intan Tiar; Wijaya, I Made Mahaputra; Arnata, I Wayan (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 10 No 2 (2022): JuniDO - 10.24843/JRMA.2022.v10.i02.p08, 2022)
The aim of this research was to determine the growth phase curve of BU3.111E1 and to determine the  effect of various pH and temperatures on BU3.111E1 isolate growth media to produce ethanol. These experiment was carried out in stages, namely culture stock rejuvenation, culture grow and adjustment, measuring the effects of various pH and temperature in media upon fermentation followed by distillation. This study used two variations of pH (4.0 and 5.0) and three variations of temperature (18, 24 and 30°C) and two repetitions.  The growth curve of BU3.111E1 isolate showed that the isolate grew in 33 hours, starting from the exponential phase, stationary phase to the death phase. The fermentation results showed that, pH 4.0  at 30°C produced the highest ethanol which was 15.05 mL with a total dissolved solids of 2.50 (?% brix). pH 5.0 at 18°C ??was produced the lowest ethanol, which was 3.47 mL with a total dissolved solids of 0.65 (?% brix). The results indicate that pH and temperature affect bacteria during fermentation to produce ethanol.